Synthesis and Nanoscale Characterization of LiNbO3 Thin Films Deposited on Al2O3 Substrate by RF Magnetron Sputtering under Electric Field - R.N. Zhukov; D.A. Kiselev; K.D. Shcherbachev; M.I. Voronova; S.V. Ksenich; I.V. Kubasov; A.A. Temirov; N.G. Timushkin; M.V. Chichkov; A.S. Bykov; M.D. Malinkovich; Yu.N. Parkhomenko (Журнал нано- та електронної фізики)
LiNbO3 thin films were deposited on Al2O3 substrates by RF-magnetron sputtering with in-situ electric field to study the self-polarization effect. The films have been characterized crystallographically by x-ray diffraction, and morphologically by atomic force microscopy. The films contain crystallites of LiNbO3 with preferable orientation [012] along the normal to the Al2O3 substrate surface (012). Piezoresponse force microscopy was used to study vertical and lateral polarization direction in LiNbO3 thin films. The analysis of the histograms of vertical piezoresponse images allowed to reveal self-polarization effect in films. The local piezoelectric hysteresis performed on the nanometer scale indicates switching behavior of polarization for LiNbO3 thin film.